Sport Business in Leading Economies. - Zhang, James J. (Emerald Publishing Limited, 2017)
From a renowned group of international scholars, this new work examines how leading economic countries use sport business to drive and further economic development by raising brand awareness (country as a brand), transforming lagging communities, and enhancing travel and tourism in the country.
Keywords: Sports -- Economic aspects.; elektronické knihy; electronic books